Distance-restrained atmospheric parameters correction (DR-APC) model for GB-SAR transmission power attenuation compensation in bridges dynamic deflection measurement. (December 2022) - Wang, Runjie; Zhang, Tong; Liu, Xianglei; Lu, Zhao; Guo, Tongxin
Highlights: A high-accuracy ground-based synthetic aperture radar measurement method. A distance-restrained atmospheric parameters correction (DR-APC) model is presented, which is derived with restrictions of the propagation distance, the height from the radar unit to the lower surface of the bridge, and the elevation angle of radar unit. The distance-restrained part in the proposed model is acquired by using the static experimental method. The efficacy of the proposed DR-APC model has been validated through dynamic deflection measurements in three bridges experimental areas. It proves that the proposed DR-APC model is effective and helpful to promote the application of GB-SAR in bridge health monitoring. Abstract: A distance-restrained atmospheric parameter correction (DR-APC) model is presented in this study to reduce the influences of atmospheric parameters and electromagnetic wave power attenuation on dynamic deflection measurement of bridges using ground-based synthetic aperture radar (GB-SAR). The proposed model considers electromagnetic wave transmission distance together with factors of bridges geometric configuration, instrument layout and atmospheric refractive index. First, the theoretical DR-APC model is derived with restrictions of the wave propagation distance, the height from radar unit to bridge lower surface and the elevation angle of radar unit. Second, the DR-APC model is determined based on continuous time-series displacement of 12 corner reflectors fixed on tripods in a stable environment area. Finally, the DR-APC model is applied to GB-SAR monitoring signals of three bridges to verify its effectiveness. The results show that the proposed model has an ability to improve the accuracy of dynamic deflection measurement using GB-SAR.